Integrated planning policies for the ecological territories and ecocities: Implementation of a smart sustainable approach. - Aragona, Stefano (Springer, 2018)
The paper, which reports research started in 1987 and extending until the recent European Regional Science Association Congresses, about innovation and anthropization processes, focuses on the word crisis. This offers a chance to move from the industrial and mass town towards a more sustainable way of anthropization. Human wisdom must consist of considering local conditions, not as design constraints, but as suggestions for plans and projects: i.e., starting from the place, from geomorphologic elements, historical events etc., with the responsibility of all actors involved in the organization and physical structure of territory and towns. This concept was developed by Salvatore Settis, reminding the fundamental role played by context. It means overcoming the industrial paradigm evolving over 350 years to built another developmental path. Calabria presents an important opportunity to propose novel territory based on man-nature alliance. This can be accomplished in harmony with the philosophy of smart city, i.e., realizing local inclusive communities that are sustainable, both materially and socially. The paper illustrates this general picture, highlighting opportunities for a different scenario by referring to the Reggio Calabria Metropolitan case. It stresses the need for a 'cultured technology' to overcome an unsustainable development. Such a culture must be based on integrated planning, able to connect rural and not rural areas, small, medium, big towns and metropolitan areas. Moreover this requires diffusion of those fundamental elements to continue advocacy of an 'ecological approach' based on knowledge of local conditions, both material and social. After a short introduction, the paper, using the 'phenomenological' methodology, describes facts and provides scenarios and operative hypotheses.
Keywords: Stadtplanung; Regionalplanung; Regionalpolitik; Umweltverträglichkeit; Nachhaltige Mobilität; Zersiedlung